Chemical respiratory sensitization—Current status of mechanistic understanding, knowledge gaps and possible identification methods of sensitizers - Hargitai, Rita; Parráková, Lucia; Szatmári, Tünde; Monfort-Lanzas, Pablo; Galbiati, Valentina; Audouze, Karine; Jornod, Florence; Staal, Yvonne C. M.; Burla, Sabina; Chary, Aline; Gutleb, Arno C.; Lumniczky, Katalin; et al. (Frontiers in Toxicology, 2024)
Respiratory sensitization is a complex immunological process eventually leading to hypersensitivity following re-exposure to the chemical. A frequent consequence is occupational asthma, which may occur after long latency periods. Although chemical-induced respiratory hypersensitivity has been known for decades, there are currently no comprehensive and validated approaches available for the prospective identification of chemicals that induce respiratory sensitization, while the expectations of new approach methodologies (NAMs) are high. A great hope is that due to a better understanding of the molecular key events, new methods can be developed now. However, this is a big challenge due to the different chemical classes to which respiratory sensitizers belong, as well as because of the complexity of the response and the late manifestation of symptoms. In this review article, the current information on respiratory sensitization related processes is summarized by introducing it in the available adverse outcome pathway (AOP) concept. Potentially useful models for prediction are discussed. Knowledge gaps and gaps of regulatory concern are identified.